Physical condition levels of futsal extracurricular students at YLPI Perhentian Marpoyan Junior High School - Pamungkas, Galuh Rahman; Jatra, Rices; Németh, Zsolt (Journal of Applied Movement and Sport Science, 2025)
Background The background of this research lies in the need to understand the physical condition of students participating in futsal extracurricular activities, as optimal physical fitness is essential for supporting performance in a fast-paced sport such as futsal. Evaluating students’ physical condition is necessary to identify their strengths and weaknesses across several fitness components relevant to gameplay. Objectives The objective of this study was to determine the overall level of physical condition among futsal extracurricular students at YLPI Perhentian Marpoyan Junior High School. Methods This research employed a descriptive quantitative design. The participants consisted of 15 futsal extracurricular students selected through a total sampling technique. Data were collected through a series of physical fitness tests, including a 30-meter sprint test to measure speed, a shuttle run test to assess agility, a standing long jump test to measure leg explosive power, a wall squat test to measure muscular endurance, and a 15-minute run test to evaluate cardiorespiratory endurance. To get an overall classification, the test results were put into standardized scoring categories and then analyzed. Results The results indicated that the students achieved an average final physical condition score of 2.5, rounded to 3, which is categorized as Fair. These findings indicate that although students possess basic physical abilities, their overall physical condition remains insufficient to meet the demands of futsal performance. Conclusion The study concludes that students require improvement through structured and consistent training, which points to the importance of enhanced fitness development programs within the extracurricular futsal setting.